DIAGNOSTIC STUDY: TRANSFORMING RESEARCH GOVERNANCE AT UNIVERSITAS JAMBI – A COMPARATIVE ANALYSIS WITH LPPM OF SEVERAL INDONESIAN UNIVERSITIES - Ade Octavia; Linda Handayani; Dwi Kurniawan (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
The Tridharma of Higher Education, encompassing Education, Research, and Community Service, serves as the cornerstone of higher education's tripartite mission. These integral functions are interdependent and mutually reinforcing, positioning universities as pivotal institutions for fulfilling societal needs in terms of quality human resources, the generation of new knowledge, and providing solutions to a myriad of societal challenges. This study aims to engage in a comparative analysis with other higher education institutions involved in Research and Community Service (LPPM) - specifically USK, UB, UNPAD, and UNHAS - to enhance the performance and governance of UNJA's LPPM. The methodology employed in this research is an interview survey. The findings indicate that USK excels in supporting researchers and offering substantial incentives. UNPAD is noted for its robust foundational data, which forms a critical basis for decision-making. Additionally, UNPAD ensures efficient facilitation of research activities and publication. The standout feature of UB is its user-friendly system, greatly simplifying processes for stakeholders. Finally, UNHAS is commended for its clear direction in research and service execution, alongside well-defined annual targets. This comparative study is instrumental in identifying best practices and potential areas for improvement in UNJA's LPPM, thereby contributing to the broader goal of enhancing the effectiveness of higher education institutions in fulfilling their Tri Dharma. Keywords: Diagnostics, Comparison, LPPM Governance